Dual-network conductive hydrogel as well as preparation method and application thereof
By using tannin acid (TA) and Fe3+ catalytic acrylic acid (PAA) polymerization on polyvinyl alcohol (PVA), the complex problem of strong and tough hydrogel synthesis in the existing technology is solved, and the strength and conductivity improvement is achieved.
Patent Information
- Application Number
- CN202411764408.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The existing strong hydrogel synthesis strategies are complex and it is difficult to build strong hydrogels through simple methods.
Using the preparation method of dual network conductive hydrogel, polyvinyl alcohol (PVA) is used as the basis of the first crosslinking network, acrylic acid (PAA) polymerization is catalyzed by redox reaction of tannin acid (TA) and Fe3+ to construct a second crosslinking network of PAA-Fe3+, and a strong PVA/PAA-Fe3+ dual network hydrogel is soaked through Fe2(SO4)3 solution.
It realizes the rapid synthesis of strong hydrogels at room temperature, with excellent mechanical properties and electrical conductivity, which is higher than that of most polyacrylic hydrogels.
Smart Images

Figure CN119529321A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer hydrogels, and in particular relates to a double-network conductive hydrogel and a preparation method and application thereof. Background Art
[0002] Hydrogels are a type of functional polymer that forms a three-dimensional network structure through physical or chemical cross-linking and can retain a large number of water molecules without being destroyed. Integrating multiple energy dissipation mechanisms in a matrix and using their synergistic effects to resist destruction to obtain strong hydrogels has become a common strategy for hydrogel synthesis. Existing strategies for the synthesis of strong hydrogels usually involve complex processes, chemical modifications, or the addition of reinforcing fillers. Therefore, it remains a challenge to construct strong hydrogels through a simple method. Summary of the invention
[0003] The purpose of the present invention is to provide a double network conductive hydrogel and a preparation method and application thereof, and to construct a strong hydrogel by a simple method, that is, to obtain a strong polyvinyl alcohol / polyacrylic acid-iron ion double network conductive hydrogel.
[0004] To achieve the above objectives, this application adopts the following technical solutions: In a first aspect, the present invention provides a method for preparing a double network conductive hydrogel, comprising the following steps: S1, dissolving polyvinyl alcohol (PVA) in deionized water, heating to 95°C with mechanical stirring for 2 h, and then cooling to 30°C to obtain a PVA aqueous solution, i.e., a first solution; S2, weighing tannic acid TA and iron sulfate Fe2(SO4)3 and dissolving them in deionized water to obtain a second solution; S3, weighing ammonium persulfate APS and dissolving it in deionized water to obtain an APS aqueous solution, i.e., the third solution; S4, measure the first solution, the second solution and the third solution in sequence, stir them evenly, then add the acrylic acid monomer AA, stir rapidly for 60 seconds, transfer the mixed solution to a culture dish, and place it at room temperature for 120 minutes; S5, soak in Fe2(SO4)3 solution for several hours to obtain strong polyvinyl alcohol / polyacrylic acid-iron ion PVA / PAA-Fe 3+ Double network conductive hydrogel.
[0005] Optionally, in step S1, the molecular weight of PVA is 5000-6000, and the mass percentage concentration of the solution is 10-15%.
[0006] Optionally, in step S2, the mass ratio of TA to Fe2(SO4)3 is 0.01-0.05, and the mass percentage concentration of the solution is 1%-5%.
[0007] Optionally, in step S3, the mass percentage concentration of the APS aqueous solution is 2%-8%.
[0008] Optionally, in step S4, the mass ratio of AA to PVA is 6:1 to 1:2.
[0009] Optionally, in step S5, the soaking time in the Fe2(SO4)3 solution is 1-6 hours.
[0010] In a second aspect, an embodiment of the present application provides a double-network conductive hydrogel, which is prepared by the preparation method of the double-network conductive hydrogel provided in the first aspect above.
[0011] In a third aspect, the embodiments of the present application disclose the use of the double network conductive hydrogel as described above as a stretchable conductor.
[0012] Compared with the prior art, the beneficial effects of the embodiments of the present application are: The present invention provides a double network conductive hydrogel and a preparation method and application thereof, which utilizes the redox reaction of tannic acid and iron ions to catalyze the polymerization reaction of acrylic acid on the basis of the first cross-linked network of PVA, thereby realizing the rapid synthesis of polyacrylic acid hydrogel at room temperature. 3+ It enters the hydrogel system through penetration and combines with the carboxylate ions on the PAA molecules to construct a metal coordination cross-linked second cross-linked network. After being soaked in Fe2(SO4)3 solution, the resulting polyvinyl alcohol / polyacrylic acid-iron ion double network hydrogel has a uniform and dense pore structure, so it has good mechanical properties, which are higher than most existing polyacrylic acid hydrogels, and has conductive properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0014] Figure 1 TA powder and PVA hydrogel provided in the embodiments of the present application, PVA / PAA-Fe before and after immersion in Fe2(SO4)3 solution 3+ Schematic diagram of the infrared spectrum of the hydrogel.
[0015] Figure 2 PVA / PAA-Fe provided in the embodiments of the present application 3+ Schematic diagram of the conductive properties of hydrogels under original, tensile, bending, and torsional deformations.
[0016] Figure 3PVA / PAA-Fe provided in the embodiments of the present application 3+ Scanning electron micrograph of hydrogel.
[0017] Figure 4 PVA / PAA-Fe without TA and with TA provided in the embodiments of the present application 3+ Schematic diagram of hydrogel.
[0018] Figure 5 The effect of immersion time on PVA / PAA-Fe in the examples of this application 3+ Schematic diagram of the effect of hydrogel mechanical properties. DETAILED DESCRIPTION
[0019] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0020] Polyvinyl alcohol (PVA) is a type of hydrophilic linear polymer containing hydroxyl groups. It has good biocompatibility, biodegradability and crystallization ability, and is widely used in the preparation of hydrogels. Polyacrylic acid (PAA) is a linear polymer formed by the polymerization of acrylic acid monomers under the action of an initiator. Although polyacrylic acid has hydrophilic groups, it cannot form a network structure by itself. It is usually chosen to introduce metal ions for physical or chemical cross-linking, which can give PAA hydrogels certain mechanical properties and good self-healing properties. However, as a physical cross-linking method, metal ion coordination has low mechanical strength, which limits its application. It is necessary to make targeted improvements.
[0021] Tannic acid (TA) is a plant polyphenol with rich catechol groups in its structure. The mutual transformation of phenol structure and quinone structure of tannic acid forms a dynamic redox system with metal ions in solution. 3+ The redox system is used to initiate the polymerization of acrylic acid, and its redox reaction can improve the efficiency of the initiator ammonium persulfate (APS) in generating sulfate radicals, thereby promoting the polymerization reaction of acrylic acid.
[0022] In view of this, the present invention provides a method for preparing a double network conductive hydrogel, using free radical polymerization and direct immersion method, using PVA as the first layer of cross-linked network basis, using TA and Fe 3+ The redox reaction of PAA initiated the polymerization of acrylic acid and the PAA was synthesized in situ at room temperature. 3+ Construction of PAA-Fe on the basis of PVA network through metal coordination 3+The cross-linked network of the second layer is then directly immersed in Fe2(SO4)3 solution to obtain a strong and tough PVA / PAA-Fe with high mechanical strength. 3+ Hydrogel. Because it contains Fe 3+ Ionic conductivity, tested for conductivity, PVA / PAA-Fe 3+ Hydrogel has certain conductive properties.
[0023] In order to illustrate the technical solution described in this application, a specific embodiment is provided below for illustration.
[0024] In some embodiments, a method for preparing a double network conductive hydrogel is provided, comprising the following steps: Step 1: Add 12 g PVA (polyvinyl alcohol) and 88 mL deionized water into a three-necked flask, heat to 95 °C and mechanically stir for 2 h, then cool to 30 °C to obtain a PVA aqueous solution with a mass fraction of 12%, i.e., the first solution; weigh 0.12 g TA (tannic acid) and 3.2 g Fe2(SO4)3 in turn and dissolve them in 80 mL deionized water to obtain a second solution; weigh 5.0 g APS (ammonium persulfate) and dissolve it in 100 mL deionized water to obtain an APS aqueous solution, i.e., the third solution; Step 2: Take 10 mL of the first solution, 4 mL of the second solution, and 0.6 mL of the third solution in sequence, stir evenly, then add 5.4 mL of AA (acrylic acid), stir rapidly for 60 s, transfer the solution to a culture dish, and place at room temperature for 120 min.
[0025] Step 3: At 0.5 mol·L -1 The tough PVA / PAA-Fe was obtained by immersing it in Fe2(SO4)3 solution for several hours. 3+ Double network hydrogel (strong polyvinyl alcohol / polyacrylic acid-iron ion double network conductive hydrogel).
[0026] As an example, based on the preparation method provided in this embodiment, PVA / PAA-Fe with different feed ratios can also be prepared according to the feed table shown in Table 1 below. 3+ Hydrogel.
[0027] Table 1 PVA / PAA-Fe 3+ Hydrogel feed schedule sample PVA / g <![CDATA[H2O / mL]]> TA / g <![CDATA[Fe2(SO4)3 / g and mass percentage / %]]> <![CDATA[H2O / mL]]> APS / g <![CDATA[H2O / mL]]> AA / mL 1 1.2 8.8 0.006 0.02 / 0.1% 4 0.03 0.6 5.4 2 1.2 8.8 0.006 0.04 / 0.2% 4 0.03 0.6 5.4 3 1.2 8.8 0.006 0.08 / 0.4% 4 0.03 0.6 5.4 4 1.2 8.8 0.006 0.12 / 0.6% 4 0.03 0.6 5.4 5 1.2 8.8 0.006 0.16 / 0.8% 4 0.03 0.6 5.4 6 1.2 8.8 0.006 0.20 / 1.0% 4 0.03 0.6 5.4 7 1.2 8.8 0.006 0.24 / 1.2% 4 0.03 0.6 5.4 8 1.2 8.8 0.006 0.32 / 1.6% 4 0.03 0.6 5.4 like Figure 1 As shown, the infrared spectrum of the double network hydrogel prepared in this example is as follows Figure 1 shown. Figure 1 In the figure, the horizontal axis represents the wave number / cm (Wavenumber / cm), and the vertical axis represents the transmittance (Transmittance). Figure 1 An analysis of what is shown is presented below.
[0028] In some embodiments, the PVA / PAA-Fe prepared above 3+ The double-network hydrogel can be used as a stretchable conductor, for example to light up an LED lamp when driven at 1.5 V.
[0029] For example, Figure 2 As shown, PVA / PAA-Fe as a stretchable conductor 3+ When the double-network hydrogel is in a state of bending, twisting, and stretching deformation with a deformation amount less than 50%, the brightness of the LED light remains almost unchanged and is almost the same as its original state.
[0030] As an example, Figure 3 PVA / PAA-Fe prepared in the above example 3+ The scanning electron microscope image of the hydrogel has a scale of 100 um. Optionally, the scanning electron microscope image also shows that the detection condition is "Regulus8100 10.0 kV 11.0 mm×300 SE (UL)".
[0031] Depend on Figure 3 It can be seen that PVA / PAA-Fe 3+ The hydrogel has a uniform and dense pore structure, so it has good mechanical properties, which are higher than most existing polyacrylic acid hydrogels, and has conductive properties.
[0032] It should be noted that the system without tannic acid TA could not form a hydrogel, but the system with tannic acid TA formed a hydrogel after 30 minutes. In the presence of oxygen, tannic acid and Fe 3+ Redox reactions occur to generate free radicals, which can act as initiators to start the polymerization of acrylic acid monomers to obtain PAA, and form a semi-interpenetrating network structure with PVA to form a gel. Figure 4 PVA / PAA-Fe without TA and with TA 3+ Schematic diagram of hydrogel. For example, Figure 4 The left side in the middle is a diagram of normal placement, and the right side is a diagram of inverted placement.
[0033] Furthermore, based on the above embodiments, in order to illustrate the technical solutions described in this application, the following embodiments are also provided for illustration. Example 1
[0034] Step 1: Add 12 g PVA and 88 mL deionized water into a three-necked flask, heat to 95 °C and stir mechanically for 2 h, then cool to 30 °C to obtain a 12% PVA aqueous solution to obtain the first solution; weigh 0.12 g TA and 3.2 g Fe2(SO4)3 in turn and dissolve them in 80 mL deionized water to obtain the second solution; weigh 5.0 g APS and dissolve it in 100 mL deionized water to obtain the third solution; Step 2: Take 10 mL of the first solution, 4 mL of the second solution, and 0.6 mL of the third solution in sequence, stir evenly, add 5.4 mL of AA, stir rapidly for 60 s, transfer the solution to a culture dish, and place at room temperature for 120 min.
[0035] Step 3: At 0.5 mol·L -1 The PVA / PAA-Fe 3+ Hydrogel.
[0036] The mechanical properties test showed that the fracture strength, elastic modulus and toughness of the hydrogel were 709.8 kPa, 234.0 kPa and 3325.3 kJ·m -3 . Example 2
[0037] Same as step 1 and step 2 of Example 1. Then, step 3 is: at 0.5 mol·L -1 The PVA / PAA-Fe 3+ Hydrogel.
[0038] The mechanical properties test showed that the fracture strength, elastic modulus and toughness of the hydrogel were 1526.9 kPa, 921.1 kPa and 6181.4 kJ·m -3 . Example 3
[0039] The same as step 1 of Example 1, and then step 2 is: measure 10 mL of the first solution, 2 mL of the second solution and 0.6 mL of the third solution in sequence, stir evenly, add 5.4 mL of AA, stir rapidly for 60 s, transfer the solution to a culture dish, and place it at room temperature for 120 min. Step 3 is: in 0.5 mol·L -1 The PVA / PAA-Fe 3+ Hydrogel.
[0040] The mechanical properties test showed that the fracture strength, elastic modulus and toughness of the hydrogel were 657.1 kPa, 575.1 kPa and 1491.0 kJ·m-3 . Example 4
[0041] The same as step 1 of Example 1, and then step 2 is: measure 10 mL of the first solution, 8 mL of the second solution and 0.6 mL of the third solution in sequence, stir evenly, add 5.4 mL of AA, stir rapidly for 60 s, transfer the solution to a culture dish, and place it at room temperature for 120 min. Step 3 is: in 0.5 mol·L -1 The PVA / PAA-Fe 3+ Hydrogel.
[0042] The mechanical properties test showed that the fracture strength, elastic modulus and toughness of the hydrogel were 1641.6 kPa, 1593.2 kPa and 3529.3 kJ·m -3 .
[0043] The following is a description of the PVA / PAA-Fe prepared in the above example. 3+ The performance of the hydrogel was evaluated.
[0044] like Figure 1 As shown, PVA hydrogel and PVA / TA-Fe3 before and after immersion + Hydrogel at 3293 cm -1 The broad absorption peak at 3382 cm belongs to the stretching vibration of alcohol hydroxyl group OH. -1 The absorption peaks are attributed to the stretching vibration of TA phenolic OH. 3+ The hydrogel became wider after soaking, indicating that the intermolecular interaction between OH and the double network polymer was enhanced.
[0045] 1245 cm -1 and 1207 cm -1 The absorption peak of PVA hydrogel is at 1076 cm -1 The absorption peak at 1065 cm-1 of PVA / PAA-Fe3+ hydrogel -1 The absorption peaks at 2940 cm-1 are attributed to the stretching vibration of the C-OH bond of the alcohol in the PVA structure. -1 The absorption peak at 1190 cm -1 The absorption peak at 1697 cm -1The absorption peak at is attributed to the ester carbonyl C=O of TA. Comparing the PVA / PAA-Fe3+ hydrogel before and after immersion, no new peaks are generated in the infrared spectrum, indicating that immersion in Fe2(SO4)3 is a process of strengthening the physical interaction of the double network hydrogel.
[0046] As shown in Tables 1 and 2, PVA / PAA-Fe with a Fe2(SO4)3 content ranging from 0.1 to 1.6% was prepared. 3+ For a series of hydrogels, when Fe2(SO4)3 is less than or equal to 0.6%, the amount of Fe2(SO4)3 used in the polymerization process has no obvious effect on the mechanical properties of the hydrogels; when Fe2(SO4)3 increases from 0.6% to 0.8%, PVA / PAA-Fe 3+ The fracture stress, elongation at break and toughness of the hydrogel also increased accordingly; when the Fe2(SO4)3 content continued to increase from 0.8%, the fracture stress of the Fe2(SO4)3 hydrogel did not change much, but the elongation at break steadily decreased. By adjusting the amount of Fe2(SO4)3 used in the PAA polymerization process, the obtained PVA / PAA-Fe 3+ Regulation of the mechanical properties of hydrogels.
[0047] Table 2 PVA / PAA-Fe with different Fe2(SO4)3 contents 3+ Breaking strength, elongation at break, elastic modulus and toughness of hydrogels sample <![CDATA[Percentage content of Fe2(SO4)3 / %]]> <![CDATA[Dosage of Fe2(SO4)3 / g]]> Breaking strength / kPa Elongation at break / % Elastic modulus / kPa <![CDATA[Toughness / kJ·m -3 > 1 0.1 0.2 861.3 337 801.6 2004.6 2 0.2 0.4 854.3 376 756.2 2256.0 3 0.4 0.8 657.1 337 575.1 1491.0 4 0.6 1.2 855.2 462 565.4 2552.3 5 0.8 1.6 1526.9 638 921.1 6181.4 6 1.0 2.0 1569.0 561 1153.7 5883.0 7 1.2 2.4 1556.1 430 1242.3 4523.1 8 1.6 3.2 1641.6 285 1593.2 3529.3 According to Tables 1 and 2 above, when the mass ratio of PVA to PAA double network is 1.2:5.4, when the TA content is 0.006 g and the Fe2(SO4)3 content is 0.16 g, the PVA-PAA-Fe 3+ The hydrogel exhibited the best mechanical properties, with the elongation at break and toughness reaching the maximum values in the test range, which were 638% and 6181.4 kJ·m, respectively. -3 , the breaking strength is 1526.9 kPa. According to the conductivity test, PVA / PAA-Fe 3+ The conductivity of the hydrogel is 0.731 S·m -1 Moreover, a series of PVA / PAA-Fe with a breaking strength of 519.9-1526.9 kPa and an elastic modulus of 172.1-1425.4 kPa were obtained within the range of 1-6 h of immersion in Fe2(SO4)3 solution. 3+ Hydrogel.
[0048] It should be noted that PVA / PAA-Fe 3+The tensile strength, elongation at break, elastic modulus and toughness of the hydrogel were significantly affected. 3+ The fracture strength of the hydrogel increased continuously from 519.9 kPa to 1505.6 kPa, while the elongation at break decreased from 1304% to 613%; the elastic modulus increased continuously from 172.1 kPa to 1425.4 kPa. 3+ The toughness of the hydrogel has been relatively good, maintaining at 3300-6000 kJ·m -3 . PVA / PAA-Fe 3+ The fracture strength of the hydrogel reached a maximum value of 1526.1 kPa when the immersion time was 5 h.
[0049] Figure 5 The results of PVA / PAA-Fe under different immersion time are given. 3+ The tensile stress-strain curve of the hydrogel, the horizontal axis represents the strain percentage (unit: %), and the vertical axis represents the stress (unit: kPa). Table 3 shows the tensile stress-strain curve of the hydrogel under different immersion times of PVA / PAA-Fe 3+ Elastic modulus and toughness of hydrogels.
[0050] Table 3 PVA / PAA-Fe at different immersion times 3+ Breaking strength, elongation at break, elastic modulus and toughness of hydrogels sample Soaking time Breaking strength / kPa Elongation at break / % Elastic modulus / kPa <![CDATA[Toughness / kJ·m -3 > <![CDATA[PVA / PAA-Fe 3+ (1 h)]]> 1 h 519.9 1304 172.1 3341.9 <![CDATA[PVA / PAA-Fe 3+ (2 h)]]> 2 h 709.8 965 234.0 3325.3 <![CDATA[PVA / PAA-Fe 3+ (3 h)]]> 3 h 793.7 805 293.7 3344.1 <![CDATA[PVA / PAA-Fe 3+ (4 h)]]> 4 h 1257.4 680 752.5 5274.7 <![CDATA[PVA / PAA-Fe 3+ (5 h)]]> 5 h 1526.1 638 921.1 6181.4 <![CDATA[PVA / PAA-Fe 3+ (6 h)]]> 6 h 1505.6 613 1425.4 6075.1 According to Table 3 above, with the increase of immersion time (1h~6h), the changing trend of the breaking strength is first increasing and then decreasing, the changing trend of the breaking elongation is gradually decreasing, the changing trend of the elastic modulus is gradually increasing, and the changing trend of the toughness is first decreasing, then increasing, and then decreasing.
[0051] In summary, the embodiments of the present application provide a double-network conductive hydrogel and a preparation method and application thereof. Polyvinyl alcohol, acrylic acid and ferric sulfate are used as the main raw materials, and tannic acid and Fe 3+ The polyvinyl alcohol / polyacrylic acid-iron ion double network hydrogel PVA / PAA-Fe 3+ The PVA / PAA-Fe prepared in the present embodiment 3+ The hydrogel has good strength, toughness and conductivity, and there is no obvious difference in the conductive properties under the tensile deformation mode, so it has potential applications in the field of stretchable conductors.
Claims
1. A method for preparing a double network conductive hydrogel, characterized in that: The following steps are involved: S1, dissolving polyvinyl alcohol (PVA) in deionized water, heating to 95°C with mechanical stirring for 2 h, and then cooling to 30°C to obtain a PVA aqueous solution, i.e., a first solution; S2, weighing tannic acid TA and iron sulfate Fe2(SO4)3 and dissolving them in deionized water to obtain a second solution; S3, weighing ammonium persulfate APS and dissolving it in deionized water to obtain an APS aqueous solution, i.e., the third solution; S4, measure the first solution, the second solution and the third solution in sequence, stir them evenly, then add the acrylic acid monomer AA, stir rapidly for 60 seconds, transfer the mixed solution to a culture dish, and place it at room temperature for 120 minutes; S5, soak in Fe2(SO4)3 solution for several hours to obtain strong polyvinyl alcohol / polyacrylic acid-iron ion PVA / PAA-Fe 3+ Double network conductive hydrogel.
2. The method for preparing the double network conductive hydrogel according to claim 1, characterized in that: In step S1, the molecular weight of PVA is 5000-6000, and the mass percentage concentration of the solution is 10-15%.
3. The method for preparing the double network conductive hydrogel according to claim 1, characterized in that: In step S2, the mass ratio of TA to Fe2(SO4)3 is 0.01-0.05, and the mass percentage concentration of the solution is 1%-5%.
4. The method for preparing the double network conductive hydrogel according to claim 1, characterized in that: In step S3, the mass percentage concentration of the APS aqueous solution is 2%-8%.
5. The method for preparing the double network conductive hydrogel according to claim 1, characterized in that: In step S4, the mass ratio of AA to PVA is 6:1 to 1:
2.
6. The method for preparing the double network conductive hydrogel according to claim 1, characterized in that: In step S5, the soaking time in the Fe2(SO4)3 solution is 1-6 hours.
7. A double network conductive hydrogel, characterized in that: The double-network conductive hydrogel is prepared by the preparation method of any one of claims 1 to 6.
8. Use of the double network conductive hydrogel as claimed in claim 7 as a stretchable conductor.
Citation Information
Patent Citations
Preparation method of high-strength stretchable PAA-Fe<3+> / AG ionic conductive hydrogel
CN113150316A
Preparation method of autocatalytic injectable hydrogel dressing for treating bacterial infection
CN115252886A
Preparation method and application of double-network conductive ion hydrogel
CN116444820A
Method for preparing double-network hydrogel tube with complex structure
US20190039269A1